Revealing the Structural Coloration of Self‐Assembled Chitin Nanocrystal Films. Issue 31 (28th June 2022) - Narkevicius, Aurimas; Parker, Richard M.; Ferrer‐Orri, Jordi; Parton, Thomas G.; Lu, Zihao; van de Kerkhof, Gea T.; Frka‐Petesic, Bruno; Vignolini, Silvia
Abstract: The structural coloration of arthropods often arises from helicoidal structures made primarily of chitin. Although it is possible to achieve analogous helicoidal architectures by exploiting the self‐assembly of chitin nanocrystals (ChNCs), to date no evidence of structural coloration has been reported from such structures. Previous studies are identified to have been constrained by both the experimental inability to access sub‐micrometer helicoidal pitches and the intrinsically low birefringence of crystalline chitin. To expand the range of accessible pitches, here, ChNCs are isolated from two phylogenetically distinct sources of α‐chitin, namely fungi and shrimp, while to increase the birefringence, an in situ alkaline treatment is performed, increasing the intensity of the reflected color by nearly two orders of magnitude. By combining this treatment with precise control over ChNC suspension formulation, structurally colored chitin‐based films are demonstrated with reflection tunable from blue to near infrared. Abstract : Chitin nanocrystals can be sustainably extracted from mushrooms and shrimp shells. These elongated nanoparticles spontaneously organize in water to form a chiral nematic mesophase. Upon evaporation, this helicoidal architecture is preserved, resulting in structurally colored films. An alkaline post‐treatment to convert chitin into chitosan is found to significantly enhance the birefringence, resulting in vibrant red, green, and blue coloration.